Urdū fikshan aur sinemā - Riz̤vānulḥaq (Ejūkeshnal Pablishing Hāʾūs, 2008)
Study on the adaptation of Urdu fiction into motion picture film
Includes index. - Includes bibliographical references (p. 239-244). - In Urdu
Keywords: Urdu fiction